The Effect Of Nursing Care Service Quality On Inpatient Satisfaction At Dr Pirngadi Hospital Medan - Lidia Silaban; Elvipson Sinaga (CV. AFDIFAL MAJU BERKAH, 2025)
Satisfaction of patients hospitalized in Dr Pirngadi Medan much experience dissatisfaction. Patient satisfaction is related to the quality of nursing care that assessment, nursing diagnosis, planning, implementation and evaluation. This study aims to determine the quality of nursing care to patient satisfaction in Dr Pirngadi Medan. This research is an analytic survey with cross sectional approach. The population is all inpatients in Dr Pirngadi Medan on average per month amounted to 138 people. Sample of 102 people, the sampling technique by means of proportional random sampling. Data collected from interviews using questionnaires, analyzed by Multiple Logistic Regression at α = 5%. The results showed that the quality assessment, nursing diagnosis, planning, implementation and evaluation of influence on patient satisfaction in hospitals Dr Pirngadi Medan and the most dominant variable influencing patient satisfaction in hospitals Dr Pirngadi Medan is variable implementation, namely on the value of the coefficient regression exp (B) 19.978. It is suggested to RSUD Dr Pirngadi Medan , to pay attention to the nurses in the room to be more active in improving the quality of nursing care in the patient, for the nurse to study more detail about the problems that emerged so that the accurate nursing diagnosis can be made, the nursing plan that has been formulated can give Quality nursing care and comprehensive, should nurses should be able to document any nursing actions that have been implemented and is expected to improve the performance of nurses so as to improve nursing care in patients.